2011
DOI: 10.1051/0004-6361/200809746
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse interstellar bands in Upper Scorpius: probing variations in the DIB spectrum due to changing environmental conditions

Abstract: Aims. We study the effects of local environmental conditions affecting the diffuse interstellar band (DIB) carriers within the Upper Scorpius subgroup of the Sco OB2 association. The aim is to reveal how the still unidentified DIB carriers respond to different physical conditions prevailing in interstellar clouds, in order to shed light on the origin of the DIB carriers. Methods. We obtained optical spectra with FEROS on the ESO 1.52 m telescope at La Silla, Chile, and measured the equivalent widths of five DI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
178
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(203 citation statements)
references
References 95 publications
(193 reference statements)
23
178
2
Order By: Relevance
“…This is very likely also caused by environment effects, since those bands are strongly influenced by the radiation field. The same remarks apply to the correlation coefficients measured by Vos et al (2011) for the upper Scorpius region that, except for DIB 5797, are lower than found here. Josafatsson & Snow (1987) computed Pearson coefficients for three DIBS in common, 5780, 5849, and 5797 Å, using early-type target stars in reflection nebulae.…”
Section: Correlation With the Color Excesssupporting
confidence: 71%
See 1 more Smart Citation
“…This is very likely also caused by environment effects, since those bands are strongly influenced by the radiation field. The same remarks apply to the correlation coefficients measured by Vos et al (2011) for the upper Scorpius region that, except for DIB 5797, are lower than found here. Josafatsson & Snow (1987) computed Pearson coefficients for three DIBS in common, 5780, 5849, and 5797 Å, using early-type target stars in reflection nebulae.…”
Section: Correlation With the Color Excesssupporting
confidence: 71%
“…Many of them are significantly or weakly correlated with interstellar integrated quantities, namely the HI, H 2 column or the color excess, as shown by numerous studies (e.g. Friedman et al 2011;Vos et al 2011). In particular, the correlation of the DIB strength with the extinction or the color excess has been investigated for a large number of bands, and it has been shown that the degree of correlation is highly variable among the DIBs (see e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Given the value of the ratio between these two DIBs as a tracer of the characteristics of the environment (i.e. radiation field) (Cami et al 1997;Vos et al 2011;Cordiner et al 2013), there is a strong motivation for a similar work to the one presented here for this spectral range. Likewise, the DIB at λ6614 is relatively strong and, as such, the creation of synthetic spectra in this spectral range should be contemplated, though a preliminary exploration of this range, not discussed here, points towards a need for a more delicate approach, where for some stellar lines, additional parameters other than log(g f ) should be tuned and/or effects like departures form LTE, explored.…”
Section: Discussionmentioning
confidence: 83%
“…However, DIBs seem sensitive to the radiation field of these stars (Vos et al 2011;Dahlstrom et al 2013;Cordiner et al 2013), and therefore hot stars are not the optimal targets to prove the typical conditions of the general ISM of our Galaxy. In fact, Raimond et al (2012) showed how using cooler target stars correlations between DIBs (and reddening) improve, confirming that the radiation field of UV bright stars has a significant influence on the DIB strength.…”
Section: Introductionmentioning
confidence: 99%
“…The DIB at λ5797.1 was not included in the fit since we did not see any evidence for it in our spectra. It is known that the ratio of the equivalent width of these two DIBs can vary up to a factor ∼5, depending on the characteristics of the ISM in the sight line of consideration (Vos et al 2011), but only in very specific situations both DIBs are comparable. Typically, the DIB λ5797.1 is ∼3-5 times fainter.…”
Section: Feature Fittingmentioning
confidence: 99%